A Novel Method for Vector Control of Faulty Three-Phase IM Drives Based on FOC Method - Mohammad Jannati; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This paper proposes a novel method for vector control of faulty three-phase Induction Motor (IM) drives based on Field-Oriented Control (FOC) method. The performance characteristics of the presented drive system are investigated at healthy and open-phase fault conditions. The simulation of the case study is carried out by using the Matlab/M-File software for a star-connected three-phase IM. The results show the better performance of the proposed drive system especially in reduction of motor speed and torque oscillations during open-phase fault operating.